UI/UX design of the PDBI digital art gallery web application using design thinking method - Khadijah, Khadijah; NA, Charmiyanti; Choiriyati, Nur; Sanwasih, Mochamad; Pohan, Amir Hamzah; Husna, Rahmatul (Priviet Social Sciences Journal, 2023)
Documentation of digital artwork is essential for designers, serving as a copyrightable asset that can be included in a student's portfolio. User interface design is chosen as the gateway for developing the PDBI Digital Art Gallery Application. It is anticipated that a well-designed user interface will be part of the feasibility analysis for further development into a comprehensive and beneficial application. The research method employed in this study is design thinking, involving the construction of a user interface and usability testing for the PDBI digital art gallery application using a qualitative approach with a case study research type. Data collection techniques include observation, competitor analysis, and questionnaire distribution to obtain user experience feedback on the application. The introduction of the PDBI Digital Art Gallery application is expected to enable PDBI students to easily archive, showcase, sell, and create digital works, empowering student digital products as intended.